Tumor-microenvironment triggered Mn-Gd based nanosystem for breast carcinoma suppression via synergistic radiotherapy and glutathione-depleting along with glucose oxidase combination enhanced Ros storm - Yonghui Su; Dongqun Guo; Yinghao Liang; Tuerdimaimaiti Meiheriban; Siyu Chen; Qian Tang; Xiqian Chen; Yan Huang; Jianqiao Zhong; Zongjunlin Liu (Journal of Nanobiotechnology)
Abstract Background Cancer treatment commonly involves radiation as a primary therapy, affecting nearly two-thirds of patients. The use of combination therapies is gaining traction, with the aim of achieving synergistic effects through the pharmacological interactions of multiple treatments. Methods and results In this study, we present a Mn-Gd-based bimetallic nanoplatform resembling a virus, designed with a rough surface for anchoring glucose oxidase enzymes (GOx) and coating with extracellular vehicles (EVs) on the outer layer (VMn-Gd@GOx-EVs). This platform enables a synergistic approach by combining radiation therapy (RT) with oxidative therapy. The nanoplatform offers four key benefits: targeted delivery to tumors through EVs, Mn and Gd ion release triggered by the tumor microenvironment, GOx-induced generation of H2O2 and acidic conditions for subsequent Fenton-like reactions, and relief from hypoxia to enhance RT. Conclusion Remarkably, the VMn-Gd@GOx-EVs platform effectively induces cell death in breast carcinoma models both in vitro and in vivo by harnessing the combined effects of RT and reactive oxygen species (ROS) generated by Mn ion catalysis under X-ray irradiation. Moreover, with its magnetic resonance imaging capabilities, this multi-functional diagnostic and therapeutic platform shows significant potential for clinical tumor treatment.